THU0109 Vaccination Rates in Adults with Autoimmune Inflammatory Rheumatic Diseases and The Patients' Perspective on Their Infection Risk. (15th July 2016) - Magro, R.; Rogers, M.; Camilleri, F.
Abstract : Background: Patients suffering from autoimmune rheumatic diseases are at increased risk of developing infections, especially if they are on immunomodulatory treatment. Objectives: The aim of the study was to determine whether vaccination in adult patients with autoimmune inflammatory rheumatic diseases (AIIRD) attending the Rheumatology Clinic at Mater Dei Hospital, is in concordance with the European League Against Rheumatism (EULAR) guidelines. Methods: 60 patients with AIIRD attending the Rheumatology Clinic were recruited for the audit. Demographic data and vaccination status were completed using the medical notes. Further information on their vaccination history and their perceived importance of vaccination was obtained by interviewing the patients. Approval to carry out this study was obtained from the University Research Ethics Committee. Results: The study included patients with a variety of AIIRD including rheumatoid arthrtitis, systemic lupus erythematosus, ankylosing spondylitis and psoriatic arthritis. 58% were females and the mean age was 62.4 years (range 24 to 81 years). Out of the 60 patients audited, 43 were on a synthetic disease modifying anti-rheumatic drug (sDMARD) alone, 6 were on a biologic drug alone, and 3 were on a combination of both a biologic drug and sDMARD. 13 patients were on glucocorticoids; of which 12 were also receiving a sDMARD. Information on vaccination history was found in the medical notes in only 2 cases. The influenza vaccine was taken in 44 patients (73.3%) of which it was taken yearly in 30 patients. Out of those who had taken the influenza vaccine, most of them claimed they had been advised to do so either by their general practitioner (43.2%) or through public health campaigns (27.3%). 32 patients (53.3%) claimed that they had the intention to take it the following year. The proportion of patients who took the influenza vaccine yearly was significantly higher in those above 65 years (p<0.001) and in those who had co-morbidities (including lung disease, diabetes and ischaemic heart disease) (p=0.024). 5 patients (8.3%) claimed they had taken the pneumococcal vaccine. All of these claimed they had been advised to do so by a hospital doctor. 38.3% claimed that they knew that they were at increased risk of infections because of their condition or treatment. Only 6.7% stated that they had been advised to take vaccination because of this. Conclusions: Even though this study may have under-estimated vaccination rates and advice given to patients because of recall bias, it has clearly shown that improved patient education on their infection risk and need for vaccination is required. This can be encouraged by having structured documentation of patients' vaccination status in the medical notes and by raising awareness of its importance within the Rheumatology Department. References: Van Assen S, Agmon-Levin N, Elkayam O et al. EULAR recommendations for vaccination in adult patients with autoimmune inflammatory rheumatic diseases. Ann Rheum Dis 2001; 70:414–422. Disclosure of Interest: None declared